2019
DOI: 10.1111/jce.14104
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 4q25 variants and biomarkers of myocardial fibrosis in patients with atrial fibrillation

Abstract: Introduction Little is known about how genetic predisposition and fibrosis relate in atrial fibrillation (AF). Hence, we sought to determine whether the genetic variants and biomarkers for fibrosis enhance prediction of outcomes after catheter ablation. Methods and Results Consecutive patients who underwent catheter ablation of AF (paroxysmal, 158; nonparoxysmal, 137) or supraventricular tachycardia without AF (n = 70) were studied retrospectively. Plasma levels of transforming growth factor β1 (TGF‐β1), tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…A previous study suggested that the preoperative and postoperative value of HA in the blood is a useful new index for AF occurrence after coronary artery bypass grafting 29 . TGF‐β1 is associated with AF severity and prognosis after catheter ablation 30,31 . Regression analysis in previous studies consistently revealed that TGF‐β1 was a major risk factor for AF recurrence and may help identify patients likely to have better outcomes after catheter ablation 32,33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study suggested that the preoperative and postoperative value of HA in the blood is a useful new index for AF occurrence after coronary artery bypass grafting 29 . TGF‐β1 is associated with AF severity and prognosis after catheter ablation 30,31 . Regression analysis in previous studies consistently revealed that TGF‐β1 was a major risk factor for AF recurrence and may help identify patients likely to have better outcomes after catheter ablation 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…29 TGF-β1 is associated with AF severity and prognosis after catheter ablation. 30,31 Regression analysis in previous studies consistently revealed that TGF-β1 was a major risk factor for AF recurrence and may help identify patients likely to have better outcomes after catheter ablation. 32,33 In summary, as a prospective study, this study measured the expression of lncRNA PVT1 in the plasma of AF patients for the first time and explored the role of PVT1 level in AF diagnosis and recurrence after RFA using the ROC curve.…”
Section: Discussionmentioning
confidence: 99%
“…100,104 This variability may be explained in part by variation in increased levels of circulating biomarkers of myocardial fibrosis in patients with paroxysmal AF. 105 Of note, there is emerging evidence that other SNPs at 4q25 may increase left atrial scar formation and increase nonpulmonary vein triggers for AF recurrence, which may help inform future risk stratification when selecting patients for catheter ablation. 106 However, prospective analyses of these and other SNPs are still needed.…”
Section: Clinical Management Considerationsmentioning
confidence: 99%
“…There is some conflicting data in another European population the rs10033464 SNP was associated with AF recurrence postablation 92 and in meta‐analysis 103,105 . This variability may be explained in part by variation in increased levels of circulating biomarkers of myocardial fibrosis in patients with paroxysmal AF 106 . Of note, there is emerging evidence that other SNPs at 4q25 may increase LA scar formation and increase nonpulmonary vein triggers for AF recurrence, which may help inform future risk stratification when selecting patients for catheter ablation 107 .…”
Section: Clinical Management Considerationsmentioning
confidence: 99%
“…103,105 This variability may be explained in part by variation in increased levels of circulating biomarkers of myocardial fibrosis in patients with paroxysmal AF. 106 Of note, there is emerging evidence that other SNPs at 4q25 may increase LA scar formation and increase nonpulmonary vein triggers for AF recurrence, which may help inform future risk stratification when selecting patients for catheter ablation. 107 However, prospective analyses of these and other SNPs are still needed.…”
Section: Clinical Management Considerationsmentioning
confidence: 99%